The interconversion of conformers of phenylalanyl-tRNA with different affinity to 70S ribosomes of Escherichia coli. - Kirillov, S V (Nucleic Acids Res, 1978)
Earlier the existence of two conformers of Phe-tRNAPhe of E. coli was demonstrated because one of them yields complexes with 70S-poly(U) of extremely high affinity and the other with at least a 105 lower binding constant. We denote the first conformer as HAC (high affinity conformer) and the second as LAC (low affinity conformer). This high difference in binding constants was used for studying the process of reversible interconversion of conformers of Phe-tRNAPhe. The transition kinetics of LAC to HAC in conditions when the latter is stable (in the presence of magnesium ions) was studied and a high value of activation energy (35 kcal/mole) found. The interconversion is the first order reaction and equilibrium does not depend of overall Phe-tRNA concentration.